2022
DOI: 10.3389/fonc.2022.943085
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein-guided surgery for the resection of pilocytic astrocytomas: A multicentric retrospective study

Abstract: ObjectivePilocytic astrocytomas (PAs) are relatively benign tumors, usually enhancing on post-contrast MRI and often characterized by a mural nodule within a cystic component. Surgical resection represents the mainstay of treatment, and extent of resection (EOR) is associated with improved survival. In this study, we analyzed the effect of sodium fluorescein (SF) on the visualization and resection of these circumscribed astrocytic gliomas.MethodsSurgical databases at two neurosurgical departments (Fondazione I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…During the last years SF has emerged as intraoperative tracer able to improve brain-tumor visualization ( 14 16 ), due to its vascular, non-specific mechanism of action related to the accumulation in brain regions with BBB disruption ( 9 , 12 ): these areas present an altered permeability that seems to correlate consistently with the contrast enhanced portions of T1-weighted MRI sequences, accounting for the staining capacity of this fluorescent tracer with tumors that uptake contrast ( 21 ). Previous experiences had suggested that the use of SF could be associated with a bright fluorescence of the tumor area in primary and recurrent high-grade gliomas ( 14 , 15 , 20 , 29 ), in brain metastases ( 17 ), in primary CNS lymphomas ( 18 ), in gangliogliomas ( 16 ), and recently in the similar entity of circumscribed astrocytic gliomas which are the pilocytic astrocytomas ( 30 ): this was also associated with good results in term of extent of resection as well as PFS and OS. In particular, in the heterogeneous group of PA, a maximal safe resection was reached in more than 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…During the last years SF has emerged as intraoperative tracer able to improve brain-tumor visualization ( 14 16 ), due to its vascular, non-specific mechanism of action related to the accumulation in brain regions with BBB disruption ( 9 , 12 ): these areas present an altered permeability that seems to correlate consistently with the contrast enhanced portions of T1-weighted MRI sequences, accounting for the staining capacity of this fluorescent tracer with tumors that uptake contrast ( 21 ). Previous experiences had suggested that the use of SF could be associated with a bright fluorescence of the tumor area in primary and recurrent high-grade gliomas ( 14 , 15 , 20 , 29 ), in brain metastases ( 17 ), in primary CNS lymphomas ( 18 ), in gangliogliomas ( 16 ), and recently in the similar entity of circumscribed astrocytic gliomas which are the pilocytic astrocytomas ( 30 ): this was also associated with good results in term of extent of resection as well as PFS and OS. In particular, in the heterogeneous group of PA, a maximal safe resection was reached in more than 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the recent availability of an integrated and speci c lters in the surgical microscope has contributed to the wide diffusion of uorescein [14][15][16]. Previous experiences suggested that the use SF could be associated with a bright uorescence of the tumor area in HGG [20], in metastases [27], in gangliogliomas [28], in pilocytic astrocytomas [29] and in spinal intramedullary lesions [30]. This was also associated with good results in term of extent of resection as well as progression free and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…4). The role of SF in low-grade tumors is still debated in the literature, although a progressive number of series are reporting positive results in these groups [19], [21]. SF appears as one amongst several new tools, like intraoperative imaging and monitoring, helping to enhance the accuracy of tumor resection.…”
Section: Sodium Uorescein Utility In Pediatric Neuro-oncologymentioning
confidence: 99%
“…extravasation [14]. Its role in high-grade gliomas (HGG) has been repeatedly suggested [15], but some literature articles also reported its use in other malignant or benign conditions [16]- [21], as well as in exclusively pediatric populations [22], [23], generally without any type of adverse reaction. However, a de nitive statement about feasibility and utility of SF in pediatrics has not been formulated yet.…”
Section: Introductionmentioning
confidence: 99%